An Empirical Analysis of Artificial Intelligence Adoption and Workforce Outcomes among Healthcare Professionals - Amol Ramrao Vande; Pratap Desai; Vinayak Shitole; Shrikant Waghulkar (Public Health, 2026)
Artificial intelligence is increasingly embedded in clinical and healthcare work processes, reshaping how healthcare professionals perform, experience, and manage their roles. AI-enabled systems such as clinical decision support, diagnostic tools, and patient management systems are increasingly transforming healthcare delivery. While AI adoption is often associated with improvements in clinical efficiency and patient care outcomes, its influence on workforce outcomes remains uneven and insufficiently examined at the individual level. This study empirically examines the impact of AI-enabled work on workforce outcomes among healthcare professionals, including doctors, nurses, and technicians, using a regression-based analytical approach. Primary data were collected from 275 healthcare professionals through a structured questionnaire, and multiple regression analysis was employed to assess the combined influence of workforce-related factors on overall workforce outcomes. Career growth opportunities show a positive influence, while factors related to workload intensity, autonomy, and learning pressure present challenges. The findings further indicate that workforce outcomes are closely linked with patient care quality and diagnostic efficiency, suggesting that the implications of AI extend beyond employees to healthcare service delivery. The study confirms that artificial intelligence adoption has a statistically significant impact on workforce outcomes among healthcare professionals. The results suggest that the effects of AI depend largely on how clinical work is designed, managed, and supported within healthcare organizations. The study offers empirical evidence to support workforce-centered AI adoption strategies and contributes to informed managerial and policy decision-making in the healthcare sector.